Analisis Keberhasilan Penanganan Air Asam Tambang Berdasarkan Parameter pH, TSS, Fe dan Mn pada KPL AL 01 PT Bukit Asam, Tbk - Irwan Ferdian (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Irwan F. 2020. Analysis of the succes of acid mine drainage treatment based on parameters pH, TSS, Fe and Mn in KPL AL 01 PT Bukit Asam, Tbk. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The degradation in river water quality was triggered by the disposal of mining industry waste water that did not accordance with environmental quality standards. This has caused the damage to the aquatic biota ecosystem. The purpose of this research was to determine the effective handling of acid mine drainage which refers to the required quality standards so that it does not pollute the environment. This research was conducted using field observation methods, data collection, laboratory analysis, application of neutralization and coagulation methods and company monitoring documents collection compared to the quality standards issued by the Governor of South Sumatra Regulation Number 08 Year 2008 covering pH parameters, TSS, Fe and Mn. These are results from the research. First, PT Bukit Asam, Tbk produces liquid waste from production activities in Pit Air Laya with characteristics pH 4.28, Total Suspended Solid (TSS) 577 mg/l, Fe 9.1 mg/l and Mn 6.4 mg/l, pumped into a mud settling pond with a rate of blow 0.73 m3/sec. Second, the liquid waste is processed by adding 0.007 gr/l quicklime, 0.6 ml/l NaOH and 0.03 g/l kuriflok. Third, the waste water of PT Bukit Asam, Tbk has met the environmental quality standard requirements by the parameters of pH 7.6, TSS 6 mg/l, Fe 0.8 mg/l and Mn 0.6 mg/l. The results was obtained show that by giving amount of chemicals precisely, will delivere a quality of waste that accordance with the environmental quality standards so that it does not pollute the river as the receiving water body.